Assembling the Local Politics of Noncitizenship: Contesting Access to Healthcare in Toronto-Sanctuary City. (16th November 2020) - Landolt, Patricia
Abstract: The article presents a case study of precarious noncitizen healthcare politics based on participant observation and interviews conducted between 2009 and 2012, as well as on documentary evidence collected during this period and up to 2016. It examines how state regulations, social networks, cultural narratives, and discretion come together to assemble the terms of access to healthcare for migrant noncitizens. Analysis shows how local contestation over healthcare policies, procedures and delivery practices contribute to the production of the formal and substantive boundaries between and within citizenship and noncitizenship. The case study identifies how precarious legal status and illegality inform the regulatory incongruencies and discursive fragility of Canada's liberal welcome for newcomers. It contributes to specifying the conceptual terrain of contemporary battles over the terms of membership for migrant noncitizens in the Global North.